2021
DOI: 10.3389/fped.2021.752123
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Biomarkers in Children and Adolescents With Orthostatic Intolerance

Abstract: Orthostatic intolerance (OI) refers to a series of symptoms that occur during upright standing, which can be relieved when returned to the supine position. OI is a common cause of syncope in children and adolescents. In recent years, more and more studies have been carried out to assess the prognosis of OI by using biomarkers, among which, flow-mediated vasodilation, left ventricular ejection fraction and fractional shortening, hemodynamic change during head-up tilt test, detection of 24-h urinary sodium excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[18] The prognostic outcomes for children with POTS under ORS treatment are different by sex. [12,13] Although the currently reported biological markers have been documented to be clinically effective in guiding the precise treatment of POTS in children, [19] the relationship between the sex and the prognosis of POTS in children has not yet been reported in the literature. [1,20] In our analysis of the dataset, we found that males had a better prognosis than females' children with POTS.…”
Section: Discussionmentioning
confidence: 99%
“…[18] The prognostic outcomes for children with POTS under ORS treatment are different by sex. [12,13] Although the currently reported biological markers have been documented to be clinically effective in guiding the precise treatment of POTS in children, [19] the relationship between the sex and the prognosis of POTS in children has not yet been reported in the literature. [1,20] In our analysis of the dataset, we found that males had a better prognosis than females' children with POTS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some investigators have reported that the number of previous episodes of syncope (4,5), onset age of syncope, and family history (6) were identified as promising predictors for recurrent syncope in VVS. In addition, others revealed that venous blood routine hemoglobin concentration and mean corpuscular hemoglobin were candidate biomarkers in predisposition to syncope recurrence (7). Further, heart rate variability (HRV), body mass index (BMI), and therapeutic regimens can also affect the prognosis of VVS (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%